2004
DOI: 10.2116/analsci.20.561
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of a New p-tert-Butyl-calix[8]arene-bonded Stationary Phase for High-Performance Liquid Chromatography

Abstract: A new p-tert-butyl-calix [8]arene-bonded silica gel stationary phase (CABS) was prepared via 3-glycidoxypropyltrimethoxysilane as a coupling reagent for HPLC. Its structure was characterized by diffuse reflectance infrared Fourier transform spectroscopy (DRIFT), elemental analysis and thermal analysis. The chromatographic performance of new packing was evaluated by using basic, acidic and neutral aromatic compounds as probes compared with conventional ODS. The results show that the new stationary phase has an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Calix­[8]­arene monolayer shows characteristic peaks at 1470 and 1536 cm –1 which are assigned to the band of benzene ring. The peaks of C–H stretching frequency appear at 2858 and 2955 cm –1 , whereas the peaks of C–H bending frequency appear at 1295 and 1368 cm –1 . For Porphyrin monolayer, the N–H stretching frequency is found to be weak at 3350 cm –1 which contains hydrogen bonding in the condensed ring systems.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Calix­[8]­arene monolayer shows characteristic peaks at 1470 and 1536 cm –1 which are assigned to the band of benzene ring. The peaks of C–H stretching frequency appear at 2858 and 2955 cm –1 , whereas the peaks of C–H bending frequency appear at 1295 and 1368 cm –1 . For Porphyrin monolayer, the N–H stretching frequency is found to be weak at 3350 cm –1 which contains hydrogen bonding in the condensed ring systems.…”
Section: Resultsmentioning
confidence: 94%
“…The peaks of C−H stretching frequency appear at 2858 and 2955 cm −1 , whereas the peaks of C−H bending frequency appear at 1295 and 1368 cm −1 . 41 For Porphyrin monolayer, the N−H stretching frequency is found to be weak at 3350 cm −1 which contains hydrogen bonding in the condensed ring systems. The peaks at 2850−3140 cm −1 are due to C−H stretching vibrations.…”
Section: Compression Isothermsmentioning
confidence: 98%
“…As can be seen in Table 4, the elution orders for most solutes on the two packings were similar, which indicates that the same moieties of the calix [6]arenas result in the similar chromatographic selectivities for the isomers. Making a comparison between CR6BS and a p-tert-butyl-calix [8]arene-bonded phase with 0.071 mmol g −1 bond amount and similar spacer [36,37], it can also be found that the k values of the isomers on CR6BS (shown in Table 4) were small, which are mainly related to the sizes of the cavities.…”
Section: The Separation Of Position Isomersmentioning
confidence: 96%
“…The calix [4]arene was grafted on silica surface (CABS) according to the reported literature. 20,21 The preparation process is shown in Figure 1. With 100 ml toluene, 12.5 ml GPTMS, 10 g activated silica particles, and 0.25 ml triethylamine (as a catalyst) were mixed, and the mixture was refluxed for 8 h at 80 C with nitrogen protection.…”
Section: Preparation Of Imprinting Polymers With Artemisinin On Silicmentioning
confidence: 99%